RESOLUSI KONFLIK PENGEMBANGAN EKOWISATA DI DESA KINARUM - Tisha Wildayanti Ramadhini; Udiansyah Udiansyah; Arfa Agustina Rezekiah (Jurnal Sylva Scienteae, 2019)
ABSTRACT. Development of ecotourism in Kinarum Village by KPHP Tabalong and KTH Watu Murung faced obstacles from certain groups thus caused conflict. This study aims to identify the conflicts that occur in the process of ecotourism development in Kinarum Village and formulate the conflict resolution. Conflict of ecotourism development in Kinarum Village occurred between Kinarum Village Head and illegal loggers group due to perception differences and poor communication. and between KTH Watu Murung and the Illegal Loggers group due to different interest. Conflict resolution that could be done to overcome this ecotourism development conflict consists of two stages. The first stage is persuasion, mediation and empowerment. The second stage, coercion will be done if the first stage is deemed unsuccessful.Keywords: conflict; ecotourism; conflict resolution; illegal logging.ABSTRAK. Pengembangan ekowisata di Desa Kinarum oleh KPHP Tabalong dan KTH Watu Murung menghadapi hambatan dari kelompok masyarakat sehingga menyebabkan konflik. Penelitian ini bertujuan untuk mengidentifikasi konflik yang terjadi dalam proses pengembangan ekowisata di Desa Kinarum dan merumuskan resolusi konflik tersebut. Konflik pengembangan ekowisata di Desa Kinarum terjadi antara Kepala Desa Kinarum dengan kelompok penebang liar akibat perbedaan persepsi serta komunikasi yang kurang baik. dan antara KTH Watu Murung dengan Kelompok Penebang Liar akibat perbedaan kepentingan. Resolusi konflik yang dapat dilakukan untuk mengatasi konflik pengembangan ekowisata ini terdiri dari dua tahap. Tahap pertama yaitu persuasi, mediasi dan pemberdayaan. Tahap kedua, koersi atau paksaan dilakukan jika tahap pertama dianggap tidak berhasil.Kata kunci: konflik; ekowisata; resolusi konflik; penebangan liar.